(untitled) (Научни трудове на УНСС, 2024)
Due to the absence of technological advancements, it is impossible to handle the operations that regulate the multifaceted nature of knowledge for effective security on the Internet. It is difficult and complex to assemble the technology needed to efficiently and effectively defend against security threats. These challenges can be overcome by utilizing machine learning and artificial intelligence (AI) techniques. This study provides a brief overview of the applications of AI for cybersecurity via smart technologies and an assessment of the prospects for expanding protection capabilities through improved defense mechanisms. The main findings show that there are presently created AI tools that are successful in protecting data. To begin with, there are neural networks, mainly intended for shielding the outermost layer. Multiple methods using AI to resolve specific safety issues are getting traction with them. On a strategic level, however, one of the outstanding cybersecurity issues is the selection of effective protection technologies